Using digital game-based technologies in a system of studying russian as aforeign language in modern university - A. V. Matokhina; N. V. Kharlamova; O. A. Shabalina; E. A. Kulikov (Открытое образование (Москва), 2017)
According to the State Educational Standard of the Russian Federation, the main objectives of teaching Russian as a foreign language are training communication and independent working skills, learning neutral and scientific styles of speech, motivating to study at Russian universities, preparing to pass certification and qualification examinations, adapting to live in Russia, etc. One of the promising trends in teaching foreign languages is the use of educational computer games. By now, digital gamebased technologies for studying Russian as a foreignlanguage have been implemented in a number of desktop and mobile applications, however, they are all intended for teaching Russian language as a discipline, and are not focused on adapting international students who have come to a new language environment. In this article, a learning game is presentedfor studying Russian as a foreign language with immersing a user into a virtual language environment in different life situations. The game includes seven game levels; each level consists of several sections, devoted to a specific real life situation with a set of assignments of increasing complexity for writing or translating some words, phrases or sentences. For each type of assignment a template with empty text fields is used, for importing files with corresponding data and their on-screen display special functions are implemented. Such approach allows to use the same template several times for the same type of assignment or to load different files for filling out the assignment text fields, depending on the number of player’s attempts. The database of tasks, level scripts and graphical content for each section are developed. Each level is matched with a game character, accompanying the player and helping him to complete the assignments. The player can choose a character, andchoose any section of the level. The assignments are stored in a coded format, for uploading files with data matched to certain assignments, special functions are developed allowing to use the same template several times for the same type of tasks or to load different files into the text fields, depending on the number of the player’s attempt. Game code is separated from game content: scripts and levels (including backgrounds and character images) are stored in corresponding files in the game directory. In the current version of the game, the first level has been implemented, including such types of assignments as sorting words by two groups by criteria, substituting the correct preposition and selecting the right ending or declination of the word. The game interface was designed using iterative testing on the target group of international students of Volgograd State Technical University (VSTU). At present, the current version of the game is used in VSTU for training the Russian language skills, preparing for Russian language tests and exams, to improve the conversational vocabulary of international students. The aggregated results of the game application will be used to evaluate the effectiveness of the proposed technology of teaching Russian as a foreign language and to develop the next levels of the game.